Antibiotic resistance patterns of multidrug resistant bacteria in acute myeloid leukemia patients during induction treatment - Lazar Trajković; Mirjana Cvetković; Mirjana Mitrović; Zlatko Pravdić; Nikola Pantić; Nikica Sabljić; Ljubomir Jaković; Ana Vidović; Nada Suvajdžić-Vuković; Marijana Virijević (Journal of Infection in Developing Countries)
Introduction: The treatment of acute myeloid leukemia (AML) is accompanied by infectious complications, particularly during induction. The surge of multi-drug resistant (MDR) bacteria represents an additional problem for the health care of patients with AML.